Application of artificial intelligence in combating drug offences in Kazakhstan: new horizons and opportunities - Maytanov, A.M.; Suleymenov, Т.N. (Bulletin of the Karaganda University “Law Series”, 2025)
The scientific article presents an in-depth analysis of the potential applications of artificial intelligence in enhancing the investigation of criminal offenses within the Republic of Kazakhstan. The purpose of this study is to analyze the impact of the application of artificial intelligence on the process of investigation of drug offences in the Republic of Kazakhstan. To achieve the set objectives, the methods of analyzing scientific literature and data collection were used, which allowed to formulate the theoretical basis of the study and identify the key areas of AI application. A technological analysis of existing AI tools was also conducted, which helped to assess their suitability and significance for law enforcement practice. The results of the study showed that AI can significantly improve the initial stages of drug crime investigations by helping to develop an investigative algorithm, formulate investigative leads, optimize evidence collection and improve the effectiveness of internet monitoring to detect and block illegal activity related to drug distribution. The findings of the study highlight the scientific and practical value of introducing AI into pre-trial investigation of drug offences, opening new perspectives to improve the efficiency and fairness of the judicial system. The study also points to potential applications of AI in training law enforcement agencies and improving investigative techniques for the offences in question.